Brand identity on local Malay herbal toiletries packaging design as a potential tourism product / Siti Sarah Adam Wan...[et.al] - Adam Wan, Siti Sarah; Mohd Razali, Noraziah; Shamsudin, Wan Nur Khalisah; Ali, Ariff (2016)
Herbal products are gaining popularity in the worldwide market due to the believing of their medication value to users. Even in Malaysia, herbal industry is increasing and the products are highly in demand. The Malaysian government is now focusing on the herbal industry as new economic resources since in the Ninth Malaysia Plan. This study attempts to look into the local Malay herbal toiletries packaging design. Through visual assessment on Malay toiletry products' packaging design which are being displayed on the market shelves, it has been discovered that majority of the packaging design are without Malay identity presented. We argue that packaging design of the Malay herbal toiletries products can look attractive by having the Malay identity on its packaging design in making purchasing decision for tourists. This research delves into recommending packaging design by identifying the criteria expectation need. In order to improve this situation, we believe that the packaging design should adopt the Kapferer's Brand Identity Model (Kapferer, J.N 2004) that includes physique, personality, culture, relationship reflection and self-image. It is hoped that this study will improve packaging design of local Malay herbal toiletries products in the local market shelves by revealing the Malay identity.